1987
DOI: 10.1016/0042-6989(87)90007-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in visual sensitivity with age in rats with heredity retinal degeneration

Abstract: Abstract-Hereditary retinal degeneration in the Royal College of Surgeons (RCS) strain of rat has been shown to produce extensive loss of photoreceptors and a corresponding decline of the electroretinogram, ganglion cell sensitivity, and the sensitivity of the pupillary light reflex. The behaviorally measured thresholds of RCS rats, on the other hand, are reported to be comparable to those for age-matched controls. We report here, that our own behavioral measurements show a clear difference between RCS rats an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…These results suggest that, at later stages of retinal degeneration, the RCS rats lose vision due to photoreceptor degeneration. Our findings agree with previous reports regarding the time course of visual loss in the RCS rat [24,25,26,27,28]. …”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that, at later stages of retinal degeneration, the RCS rats lose vision due to photoreceptor degeneration. Our findings agree with previous reports regarding the time course of visual loss in the RCS rat [24,25,26,27,28]. …”
Section: Discussionsupporting
confidence: 82%
“…Since this is not the first time that absolute threshold has been measured behaviorally in rats (Silver, 1967;Muntz, 1967;Birch & Jacobs, 1975;Trejo & Cicerone, 1987;Kurylo et al, 1991), it is of interest to know what others have found. Unfortunately, other studies have not directly compared albino and pigmented animals.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, differences in the state of adaptation, in the spatial, temporal, and chromatic parameters of the stimuli and in how the visual stimuli were quantified make comparisons between studies problematic. The two most relevant of these (Trejo & Cicerone, 1987;Kurylo et al, 1991) used 500nm monochromatic stimuli and stated the threshold in terms of flux density at the cornea. As best as we can estimate, these thresholds correspond to -5.9 log (scotopic) cd/m 2 for albino animals (Trejo & Cicerone, 1987) and -4.35 log (scotopic) cd/m 2 for pigmented animals (Kurylo et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A popular model of RP used to examine retinal pigment epithelium (RPE) dysfunction is the Royal College of Surgeons (RCS) rat, which has been used extensively for functional, anatomical, and therapeutic studies. Indeed, numerous studies have shown that the RCS rat undergoes a progressive decay of photoreceptors and subsequent loss of visual function (DiLoreto et al, 1996; LaVail et al, 1975; McGill et al, 2004; McGill et al, 2007a; Mullen and LaVail, 1976; Perlman, 1978; Trejo and Cicerone, 1987). Although the RCS rat is a useful model for such studies, the patient population affected with the same MERTK gene mutation is relatively small, which limits the translation of research findings to clinical application.…”
Section: Introductionmentioning
confidence: 99%